Chirped solitons in discrete electrical transmission line - Houwe, Alphonse; Abbagari, Souleymanou; İnç, Mustafa; Betchewe, Gambo; Doka, Serge Y.; Crepin, Kofane T.; Nisar, K. S. (Elsevier, 2020)
I,n this paper, we investigate the solitary waves to the discrete nonlinear electrical transmission lines with resonant tunneling diode (RTD). We derive the envelope Ginzburg Landau (GL) equation to the lattice by employing reductive perturbation method in a small amplitude. We analyze the steady state of the results by using the modulation instability (MI). We also use the traveling wave transformation to investigate chirped bright and dark soliton to the GL equation. We demonstrate our results by some graphical representation in 3-D and 2-D.
Keywords: Solitary waves; Modulation instability; Discrete nonlinear electrical transmission line